Characterising and monitoring preconception health in England: a review of national population-level indicators and core data sources. (4th April 2022) - Schoenaker, Danielle A.J.M.; Stephenson, Judith; Connolly, Anne; Shillaker, Sally; Fishburn, Sarah; Barker, Mary; Godfrey, Keith M.; Alwan, Nisreen A.
Abstract: Initiatives to optimise preconception health are emerging following growing recognition that this may improve the health and well-being of women and men of reproductive age and optimise health in their children. To inform and evaluate such initiatives, guidance is required on indicators that describe and monitor population-level preconception health. We searched relevant databases and websites (March 2021) to identify national and international preconception guidelines, recommendations and policy reports. These were reviewed to identify preconception indicators. Indicators were aligned with a measure describing the prevalence of the indicator as recorded in national population-based data sources in England. From 22 documents reviewed, we identified 66 indicators across 12 domains. Domains included wider (social/economic) determinants of health; health care; reproductive health and family planning; health behaviours; environmental exposures; cervical screening; immunisation and infections; mental health, physical health; medication and genetic risk. Sixty-five of the 66 indicators were reported in at least one national routine health data set, survey or cohort study. A measure of preconception health assessment and care was not identified in any current national data source. Perspectives from three (healthcare) professionals described how indicator assessment and monitoring may influence patient care and inform awareness campaign development. This review forms the foundation for developing a national surveillance system for preconception health in England. The identified indicators can be assessed using national data sources to determine the population's preconception needs, improve patient care, inform and evaluate new campaigns and interventions and enhance accountability from responsible agencies to improve preconception health.